Evaluating the Implementation of the FinOps Framework for Cloud Infrastructure Cost Management: A Case Study of Technology Companies in Indonesia - Manurung, Hierony; Aji, Rizal Fathoni (Scientific Journal of Informatics, 2025)
Purpose: The management of cloud infrastructure costs has become increasingly relevant in light of the rapid rate of cloud service adoption, especially in Indonesia's technology space, where there is tremendous economic pressure. Cloud infrastructure cost management solutions such as the FinOps Framework are clearly intended to provide a greater degree of accountability for financial governance and to enable cloud spending optimization when implemented holistically. In this research, we want to evaluate how FinOps adoption maturity is in several technology companies, and to find the gap between FinOps Framework principles and their real-world implementation. Methods: A mixed-methods case study was employed. To gather primary data, the first step was to interview six FinOps practitioners using semi-structured interviewing methods. Thematic analysis was used to identify thematic similarities across responses. Following the development of a simplified three-point maturity score system based on the FinOps framework, we compared each participant's maturity state in reference to the variations outlined in the FinOps literature. Result: From the interviews, there was an emphasis on key processes, such as cost ownership, budgeting, and governance, which were quite centralized, reactive, and somewhat informal, although everyone was using technical optimization approaches such as rightsizing. Our quantitative analysis corroborated this, with a cohort average maturity score of only 1.53 out of 3. This indicates a general maturity score in the "Crawl" or first stage, indicating shortcomings related to the process element of the basic practices not being integrated in a systematic way.  Novelty: This research provides meaningful and helpful insights into the real challenges of tech companies in Indonesia implementing FinOps. Our research provides a clear baseline for companies working locally by measuring maturity levels and making recommendations at the end. More importantly, beyond technical optimization, it clearly identifies the need to formalise policies and to improve cooperation across functional areas. This mixed methods approach should be extended to other research by increasing sample size and allowing for a deeper exploration of the cultural context.